The evolution of political discourse of Podemos party: from populist rhetoric to the ideals of cultural war - Anastasia V. Demkina (Ибероамериканские тетради, 2017)
The article examines how the discursive framework in the speeches of the leaders of Podemos party and its documents changed over several electoral cycles (2014- 2016). A particular attention is given to indirect instruments of political strife, such as communicational, educational and cultural which Podemos applied in order to persuade the electorate.